Regulation of progesterone signaling during pregnancy: Implications for the use of progestins for the prevention of preterm birth - Byrns, Michael C. (The Journal of steroid biochemistry and molecular biology, 2014)
► The pathways for maintaining progesterone signaling during pregnancy are examined. ► Progesterone synthesis and metabolism in target tissues plays an important role. ► Expression of nuclear and membrane progesterone receptors are also key determinants. ► Pharmacotherapy with progestins reduces the risk of preterm birth. ► The two progestins used might be affected differently by the regulatory pathways. Preterm birth is a major cause of neonatal morbidity and mortality. Progesterone plays a critical role in suppressing the inflammatory signals that would induce parturition prior to term. Progesterone signaling is regulated in a variety of ways during pregnancy. Endocrine production of high levels of progesterone by the placenta ensures the availability of high levels of progesterone throughout pregnancy. Paracrine regulation of progesterone metabolism in target tissues, particularly the myometrium and cervix, also determines the amount of progesterone ligand available. Progesterone metabolism can also lead to the formation of metabolites that contribute to its effects. In particular, 5β-dihydroprogesterone formation by aldo-keto reductase 1D1 appears to play an important role in maintaining uterine quiescence. Progesterone signaling can also be regulated at the receptor level through changes in the relative expression of the nuclear progesterone receptor isoforms, reduced expression of membrane receptors, and changes in the expression levels of coactivators and/or corepressors, including nuclear factor κB. Progesterone and 17α-hydroxyprogesterone caproate (17OH-PC) have recently been shown to reduce preterm births in women with previous preterm birth or shortened cervix. It is important to realize that these two progestins are likely to act in significantly different ways, which will likely influence their efficacy. The structural differences and resistance to metabolism exhibited by 17OH-PC means that it will be unable to activate some of the pathways that progesterone activates, but that it also will not be subject to paracrine inactivation. The fact that progesterone therapy works for maintaining pregnancy in some women, indicates that for those women insufficient levels of progesterone ligand in target tissues is a determining factor in early parturition, despite high levels of circulating progesterone. This article is part of a Special Issue entitled ‘Pregnancy and Steroids’.